Development of Technique to Screen Cocoa for Resistance Against the White Root Disease Caused by Rigidoporus Lignosus (Klot.) Bres. - Che Ahmad, Azmi (2005)

(untitled)
Rigidoporus lignosus, Phellinus noxius and Ganoderma philippii, Basidiomycetous fungi commonly associated with white, brown and red root diseases respectively, were isolated from infected cocoa roots. The disease symptoms and characteristics of each fungus were identified, and the prevalence of R. lignosus and white root disease over the others was confirmed in a study of three cocoa planting areas in Peninsular Malaysia. Growth of R. lignosus on potato dextrose agar medium was significantly influenced by factors of temperature and pH. The temperature range favourable for growth was 30ºC, while the optimum pH was 5. A study was undertaken to induce production of basidiocarps of R. lignosus in vitro. Basidiocarps were formed on autoclaved and non-autoclaved soil by 14 days after incubation. Ultrastructural studies of R. lignosus basidiocarp and basidiospore were done. The viability of basidiospores were confirmed by germination on glass slides coated with malt extract agar. Artificial inoculation of R. lignosus using mycelial mats and basidiospores suspension failed to induce white root disease symptoms on cocoa seedlings. However, in this study a technique was successfully developed for screening cocoa seedlings for resistance against R.lignosus. The method involved the insertion of the tap root of 10-day old cocoa seedling into the hole of a R. lignosus colonized rubber wood block and subsequently covered in soil in a black polythene bag. Symptoms of white root disease were recorded within two weeks after inoculation and were measurable using a disease severity index. R. lignosus isolate CRD/LKM/10 was found to be the most virulent isolate as it had caused a significantly more severe white root disease infections in cocoa seedlings compared to six other R. lignosus isolates tested. The method of inoculation was subsequently used to screen cocoa seedlings of 15 selected cocoa clones (including the widely planted PBC 123 clone) for resistance against white root disease using R. lignosus isolate CRD/LKM/10 as the test fungal organism. The results revealed that cocoa seedlings of clones ICS 60 and PA300 were significantly less infected by white root disease thus indicating that they were more resistant to the disease compared to all other cocoa clones tested.